PERSEPSI, PERILAKU, DAN RESPON MASYARAKAT DESA ARJOSARI, KECAMATAN KALIPARE TERHADAP KEKERINGAN - Lilik Zuhriyah; Rahmah Dara Lufira; Satwika Desantina Muktiningsih; Aldila Putri Rahayu; Anggun Setyaningrum (Jurnal Kesehatan dan Pengelolaan Lingkungan, 2022)
occur every year. The purpose of this study is to present information regarding: community perceptions and responses to drought based on a study of the behavior patterns of the Arjosari Village community. Perception data about the drought that hits Arjosari Village every year and information about community behavior and responses to address water shortages were collected by means of Focus Group Discussions (FGD). Interviews and observations of the FGDs were conducted directly by the author. The results of the study show: 1) Drought occurs every year in the dry season and has been going on for a long time. 2) The community's perception of the drought that hit this village is a destiny that must be faced because the Arjosari Village area is a karst area and has very deep water sources 3) If the well is dry, they will ask BPBD assistance and if it is still insufficient, they will buy water . 4) The response and behavior to face drought is an obligation for them to meet their water needs in order to maintain health